Beyond Technique: Pedagogy, Culture, and Psychological Readiness in Malaysian University Silat Athletes - Mohamad Nizam Nazarudin; Wan Ahmad Munsif Wan Pa (International Martial Arts and Culture Journal, 2025)
Perspective. Traditional martial arts are increasingly incorporated into higher education as competitive and co-curricular activities; however, empirical evidence explaining how pedagogical practices influence psychological readiness and performance remains limited, particularly within culturally embedded martial traditions such as silat. Problem. Much of the existing literature prioritises biomechanical or performance-oriented perspectives, offering limited insight into the pedagogical and psychological mechanisms through which training is translated into effective competitive outcomes. This gap risks reducing silat to a culturally neutral sport and overlooks its educational and cultural foundations. Method. The purpose of this study was to examine the relationships between pedagogical practices, psychological readiness, and competitive performance among Malaysian university silat athletes, with particular attention to the mediating role of psychological readiness and the relative contribution of culturally grounded pedagogy. A quantitative, cross-sectional research design was employed involving 312 silat athletes from public universities in Malaysia. Data were collected using validated questionnaires and analysed using confirmatory factor analysis (CFA) and structural equation modelling (SEM). Results. The findings indicate that pedagogical practices have a strong, positive relationship with athletes’ psychological readiness, whereas psychological readiness, in turn, significantly predicts competitive performance. Pedagogical practices also demonstrate a weaker but significant direct effect on performance. Mediation analysis confirms that psychological readiness partially mediates the relationship between pedagogy and performance. Conclusions. Among pedagogical dimensions, cultural–philosophical integration emerges as the strongest predictor of psychological readiness. In conclusion, the study provides empirical evidence that pedagogical quality, particularly culturally grounded pedagogy, plays a central role in shaping psychological readiness and enabling consistent competitive performance among university silat athletes. Future research should adopt longitudinal designs, incorporate objective performance indicators, and extend this pedagogical–psychological framework to other traditional martial arts and cultural contexts.